Reliability tests of gated silicon field emitters for use in space - Aplin, K; Collingwood, C; Kent, B (2004)
Neutralizes are required to prevent spacecraft charging from satellite ion propulsion. This paper discusses the development of a gated silicon tip field emitter (FE) neutralizer, specified to deliver 6 mA, with each tip emitting a mean current of 7 nA. It is important to investigate factors affecting the lifetime of field emitter arrays for a space application, as longevity and reliability are both critical requirements. Semi-automated procedures to prepare 400 arrays, each consisting of 765 FEs, for life tests are described with failure conditions strictly defined by mission constraints. Results of 25 life tests on 72 arrays driven to failure at constant emission current are summarized, and a case study of one test is presented. Two of the three failure mechanisms identified are consistent with thermal failure and damage by ion bombardment. Reduced field enhancement from tip erosion caused by ion bombardment is a common explanation for FE failure. However, scanning electron microscope examination of tip apex diameters showed no significant relationship between array failure and apex geometry. The third failure mechanism was associated with short-lived arrays and may be caused by manufacturing defects. Substantial intrinsic variability was observed in the arrays tested, even with the rigorous production standards required for space applications. Arrays without manufacturing defects had lifetimes of thousands of hours.